Odpowiedzi

Najlepsza Odpowiedź!
2009-12-17T20:29:07+01:00
1. 2x(x-1)=1+2x²
2x^2 -2x = 1 + 2x^2
x = -1/2

2. 2x(x-1)-x²=(1+x)x
2x^2 -2x - x^2 = x + x^2
x=0

3. (1+x)(2-3x)=1,5x(1-2x)
2 - 3x + 2x - 3x^2 = 1,5x - 3x^2
-2,5x = -2
x = 0,8

4. (0,5x-4)x=0,25(1+2x²)
0,5x^2 - 4x = 0,25 + 0,5x^2
-4x = 0,25
x = -0,0625
1 5 1
2009-12-17T20:49:17+01:00
1. 2x²-2x=1+2x² | -2x²
-2x=1 | *(-1)
2x=1 |:2
x= ½

2.2x²-2x-x²=x+x²
x²-2x=x+x² |-x²
-2x=x
równanie sprzeczne albo tożsamościowe

3.2-3x+2x-3x²=1,5x-3x²
2-x-3x²=1,5x-3x²|-2
-x-3x²=1,5x-3x²-2|+3x²
-x=1,5x-2|-1,5x
-2,5x=-2 |*(-1)
2,5x=2|:2,5
x=2:2,5
x=2:2½
x=²/₁*⅖
x=⅘

4. (0,5x-4)x=0,25(1+2x²)
0,5x²-4x=0,25+0,5x²|-0,5x²
-4x=0,25|*(-1)
4x=-0,25|:4
x=-²⁵/₁₀₀ * ¹/₄
x=-¹/₁₆


1 5 1